The connection between bubble size spectra and energy dissipation rates in the upper ocean - Garrett, Chris; Li, Ming; Farmer, David (Journal of physical oceanography, 2000)
Garrett et al discuss Hinze's formula for the largest size that a bubble can be and still have surface tension forces holding it together against the disruptive pressure forces associated with turbulence.